2021
DOI: 10.1111/jvh.13454
|View full text |Cite
|
Sign up to set email alerts
|

High rates of sustained virological response despite premature discontinuation of directly acting antivirals in HCV‐infected patients treated in a real‐life setting

Abstract: In routine clinical practice, hepatitis C virus‐infected patients can prematurely discontinue the prescribed regimen for several reasons. The aim of our study was to investigate sustained virological response (SVR12) rates in patients who prematurely discontinued directly acting antiviral (DAA) regimens and to assess the shortest effective duration of DAA able to lead to SVR12. We retrospectively collected the SVR rates of patients, registered in the NAVIGATORE‐Lombardia Network database from January 2015, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…In comparison to previous studies, good adherence to treatment and the follow-up program was observed in our series, with no drop-outs due to toxicity[ 21 - 25 ]. In particular, Avramovic et al [ 24 ] reported a similar rate of virological response (92%) in PWIDs.…”
Section: Discussionsupporting
confidence: 49%
“…In comparison to previous studies, good adherence to treatment and the follow-up program was observed in our series, with no drop-outs due to toxicity[ 21 - 25 ]. In particular, Avramovic et al [ 24 ] reported a similar rate of virological response (92%) in PWIDs.…”
Section: Discussionsupporting
confidence: 49%